Advances in pharmacotherapy for erectile dysfunction and associated cardiac impact. (21st November 2016) - Voznesensky, Igor; DeLay, Kenneth J.; Hellstrom, Wayne J. G.
ABSTRACT: Introduction: Cardiovascular disease (CVD) and erectile dysfunction (ED) are two disease processes that affect millions of men. CVD and ED are increasingly recognized as sharing a common pathophysiologic origin. As the nature of this relationship continues to be elucidated, there is growing interest in developing a therapy to effectively target both processes. While researchers have largely focused on phosphodiesterase-5 inhibitors (PDE5Is), the established first-line therapy for ED, newer ED drugs, designed based on better understanding of the physiology of erection, may also show promise. Areas covered: This paper will review the relationship between ED and CVD, as well as the currently available and investigational pharmacologic treatments for ED. The particular focus will be on the role that these therapies play in managing CVD. Expert opinion: PDE5Is, along with the newer ED therapies, are promising candidates for managing ED and concurrently providing cardioprotection. Despite some in vitro success with PDE5Is, maxi-K channel activators, and guanylyl cyclase (GC) stimulators, in vivo studies have either been lacking, or shown conflicting results. More well designed clinical studies are needed in order to characterize an ED pharmacotherapy that offers proven cardioprotection.